Unpacking ESG disclosure and market performance: a stakeholder-based study of Indonesian Energy Firms - Agustina, Yumniati; Setiadi, Iwan; Murwaningsari, Etty (Trigin Publisher, 2025)
This scholarly work investigates the potential impact of Environmental, Social, and Governance (ESG) information dissemination on firm-level performance, within the theoretical scope of stakeholder orientation. ESG transparency is evaluated across three thematic pillars—ecological stewardship, societal engagement, and corporate oversight—based on parameters delineated by Nasdaq ESG Metrics (2019). Corporate performance is represented by a market-based indicator, namely Tobin’s Q. The empirical dataset comprises 17 energy-sector entities listed on the Indonesia Stock Exchange over the period 2019–2023, selected through purposive sampling methodology. Analytical procedures employ multiple linear regression techniques. The empirical results indicate that environmental transparency exerts a statistically significant and favorable influence on firm value. In contrast, disclosures related to social and governance aspects do not demonstrate a meaningful association with corporate performance. On the whole, the disclosure of ESG dimensions exhibits a significant and positive linkage with firm outcomes. Nevertheless, in spite of existing regulatory mandates, merely 25% of energy firms have issued sustainability reports, and the comprehensiveness of ESG-related disclosures remains suboptimal. The present invetigation highlights the strategic importance of environmental transparency in enhancing market valuation. Practically, the findings urge energy firms to enhance environmental disclosures to boost investor trust and firm valuation.